Changes in fruit pigment accumulation, chloroplast development, and transcriptome analysis in the CRISPR/Cas9-mediated knockout of Stay-green 1 (slsgr1) mutant. (30th November 2021) - Ma, Liqun; Zeng, Ni; Cheng, Ke; Li, Jinyan; Wang, Keru; Zhang, Chunjiao; Zhu, Hongliang
Abstract: The green-flesh ( gf ) mutant of the tomato fruit ripen to a muddy brown color and has been demonstrated previously to be a loss-of-function mutant. Here, we provide more evidence to support this view that SlSGR1 is involved in color change in ripening tomato fruits. Knocking out SlSGR1 expression using a clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 genome editing strategy showed obviously a muddy brown color with significantly higher chlorophyll and carotenoid content compared with wild-type (WT) fruits. To further verify the role of SlSGR1 in fruit color change, we performed transcriptome deep sequencing (RNA-seq) analysis, where a total of 354 differentially expressed genes (124/230 downregulated/upregulated) were identified between WT and slsgr1 . Additionally, the expression of numerous genes associated with photosynthesis and chloroplast function changed significantly when SlSGR1 was knocked out. Taken together, these results indicate that SlSGR1 is involved in color change in ripening fruit via chlorophyll degradation and carotenoid biosynthesis.